PENGARUH KEDISIPLINAN DAN PENGAWASAN TERHADAP KINERJA BANTUAN POLISI PAMONG PRAJA KABUPATEN BOGOR - Syaiful Anwar; Muhamad Jibril (Economicus : Jurnal Ekonomi dan Manajemen, 2021)
Supervision and Discipline is one of the efforts to improve the performance of employees/members, by managing supervision and discipline in the right way, it is expected to be able to improve the performance of employees/members in carrying out their assigned tasks properly. The purpose of this study was to determine the effect of supervision and discipline on the performance of employees/members at the Bogor Regency Civil Service Police Unit. The type of research used is causality with a quantitative approach. The location of the research is the Office of the Civil Service Police Unit, Bogor Regency. The population of the study was members of the Bogor District Civil Service Police Assistance at the Command Headquarters with a total of 150 people. In this study, sampling was carried out using the Slovin formula and the results of the sampling were 110 people. The results of the study show that supervision and discipline simultaneously have an influence on the performance of the Bogor Regency Civil Service Police Assistance, this is proven based on the results of the F (simultaneous) test which is obtained the F count value is greater than F table, F count 59,206 > F table 3.08. Based on the results of the coefficient of determination test, the Adjusted R Square value is 0.516 or 51.6%. This shows that Discipline and Supervision simultaneously contribute to influencing the Performance of Personnel by 51.6%. While the remaining 48.4% is influenced by other factors which in the study were not discussed or studied.